Effects of a riboflavin source suitable for use in organic broiler diets on performance traits and health indicators. (18th April 2020) - Lambertz, C.; Leopold, J.; Damme, K.; Vogt-Kaute, W.; Ammer, S.; Leiber, F.
Abstract : Riboflavin (vitamin B2 ) is essential for monogastric animals. It is mainly produced by recombinant microorganisms ( Candida famata, Bacillus subtilis and Ashbya gossypii ). The availability of genetically modified organism (GMO )-free riboflavin, obligatory in European organic agriculture, is a major issue. Besides, requirements for organic livestock might differ from conventional production because other genotypes and feed formulations are used. The effects of a fermentation suspension with a high native content of riboflavin produced with unmodified A. gossypii by fermentation were investigated at graded dosages as an alternative to conventional (GMO-based) riboflavin in slow-growing broilers on performance traits and health and welfare indicators. In 2 runs with 800 animals each, Ranger Gold™ broilers were fed with 4 dietary treatments. For starter diets (day 1 to 18), treatments included a basal diet (1) without any riboflavin supplementation (negative control, N-C ), (2) with conventional riboflavin supplementation (Cuxavit B2 80% riboflavin) at 9.6 mg/kg (positive control, P-C ), (3) with riboflavin supplementation from the alternative source at 3.5 mg/kg (A-low ) and (4) with riboflavin supplementation from the alternative source at 9.6 mg/kg (A-high ). For the finisher diet (day 29 until slaughtering), P-C and A-high were supplemented with 8.0 mg/kg and A-low with 3.5 mg/kg. Diets were formulated according to organic regulations. Animals were kept in floor pens with 20 chickens per pen. Weekly, BW, feed and water consumption were recorded. Every second week, animal-based health and welfare indicators (feather score and footpad dermatitis) were scored. Slaughter traits were assessed for five males and females per pen at 62/63 days of age. Final body weight of A-high differed from N-C and A-low, but not from P-C. From week 2 until six years of age, A-high had a higher daily weight gain when compared to all other groups. With 74.4%, dressing percentage was higher in A-high compared with all other groups (73.3%). Breast percentage of A-low was lower than that of both control groups but did not differ from A-high. The highest frequency of liver scores indicating fatty liver syndrome was found in P-C, followed by N-C and A-low. Feather scores did not respond to treatment; the highest frequency of mild footpad dermatitis was observed in A-high, however at a low prevalence. In conclusion, the tested fermentation suspension with a high native content of riboflavin derived from fermentation of A. gossypii can be used at levels of commercial recommendations as alternative to riboflavin produced from GMO in broiler feeding. Further studies must verify whether riboflavin can be reduced without inducing riboflavin deficiency in slow-growing broilers.